Socially responsible stocks: a boon for investors in India. Issue 2 (3rd August 2015) - Tripathi, Vanita; Bhandari, Varun
Abstract : Purpose: – The purpose of this paper is to empirically examine the performance of socially responsible stocks portfolio vis-à-vis portfolios of general companies in the Indian stock market. Design/methodology/approach: – The study has used absolute rate of return as well as various risk adjusted measures like Sharpe ratio, Treynor ratio, Jensen's α, Information ratio, Fama's decomposition measure and dummy regression model to evaluate the performance of various portfolios. Findings: – Socially responsible stocks portfolios are found to have lower relative risk despite having higher systematic risk. Further the authors find that during crisis and post-crisis period, socially responsible stocks portfolio generated significantly higher return as compared to other portfolios in the Indian stock market. Environmental, social and governance (ESG) Index and GREENEX Index provided positive net selectivity returns in all the three sub periods, especially during crisis period. GREENEX and ESG outperformed NIFTY and SENSEX even on net selectivity basis. This indicates that the compromise made with respect to diversification by investing in socially responsible stocks portfolios was well rewarded in terms of higher returns in Indian context. Practical implications: – The findings lend support to the case of socially responsible investing (SRI) in India and are relevant for companies, regulators, policy makers and investors at large. Mutual funds and other investment funds should launch schemes which invest in socially responsible stocks so as to provide the benefits of SRI even to small investors in India. Originality/value: – The study contributes to the related literature by analysing the performance of socially responsible stocks portfolios in Indian stock market which is one of the emerging markets.